Tindakan Faktual Pemerintah dalam Pelaksanaan Putusan Peradilan Tata Usaha Negara - Soeleman Djaiz Baranyanan (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2024)
This study analyzes government compliance with State Administrative Court decisions and the factual impact of such implementation in the Indonesian legal system. Given that compliance with State Administrative Court decisions is part of the supremacy of law and citizen rights, this study will explore inhibiting factors and strategies to improve compliance. Law Number 5 of 1986 concerning State Administrative Courts and its amendments regulates the government's obligations in implementing State Administrative Court decisions. In addition, Law Number 30 of 2014 concerning State Administration also contains provisions relating to the discipline and authority of state administrative officials in implementing decisions. This study uses a juridical-normative method to examine the laws and regulations governing the implementation of State Administrative Court decisions. Legal certainty is a guarantee that laws are made, interpreted, and applied in accordance with clear and logical rules, so as not to provide room for arbitrariness. An integrated legal and administrative strategy is essential to increase compliance with State Administrative Court decisions. Compliance with decisions of the State Administrative Court is an important element in ensuring the principle of the rule of law. However, in practice, the implementation of State Administrative Court decisions is often hampered by various interrelated factors. These obstacles can be categorized into three main aspects, namely normative, structural, and cultural factors.